Efficacy and Safety of Using High-Flow Nasal Oxygenation in Patients Undergoing Rapid Sequence Intubation - Raineri, Santi Maurizio (Turk J Anaesthesiol Reanim, 2017)
OBJECTIVE: To assess the efficacy and safety of high-flow nasal oxygen (HFNO) therapy in patients undergoing rapid sequence intubation (RSI) for emergency abdominal surgery. METHODS: HFNO of 60 L.min(−1) at an inspiratory oxygen fraction of 1 was delivered 4 min before laryngoscopy and maintained until the patient was intubated, and correct intubation was verified by the appearance of the end-tidal CO(2) (EtCO(2)) waveform. Transcutaneous oxygenation (SpO(2)), heart rate and non-invasive mean arterial pressure were monitored at baseline (T0), after 4 min on HFNO (T1) and at the time of laryngoscopy (T2) and endotracheal intubation (ETI) (T3). An SpO(2) of <3% from baseline was recorded at any sampled time. The value of EtCO(2) at T3 was registered after two mechanical breaths. The apnoea time was defined as the time from the end of propofol injection to ETI. RSI was performed with propofol, fentanyl and rocuronium. RESULTS: Forty-five patients were enrolled. SpO(2) levels showed a statistically significant increase at T1, T2 and T3 compared with those at T0 (p<0.05); median SpO(2)% (interquartile range) was 97% (range, 96%–99%) at T0, 99% (range, 99%–100%) at T1, 99% (range, 99%–100%) at T2 and 99% (range, 99%–100%) at T3. Minimal SpO(2) was 96%; no patient showed an SpO(2) of <3% from baseline; mean EtCO(2) at the time of ETI was 36±4 mmHg. Maximum apnoea time was 12 min. CONCLUSION: HFNO is an effective and safe technique for pre-oxygenation in patients undergoing rapid sequence induction of general anaesthesia for emergency surgery.